2009
DOI: 10.1111/j.1749-6632.2009.04048.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Receptor LGR7 (RXFP1) Is Regulated by Estrogen

Abstract: Estrogen regulates LGR7 (RXFP1) mRNA expression in an in vitro model of human term pregnancy cervix that utilizes lower uterine segment fibroblasts. LGR7 mRNA levels were increased by estradiol to mean levels of 152%+/- 5.9% above those in untreated control cells. Therefore, estradiol may amplify relaxin's actions in the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
2
6
1
Order By: Relevance
“…Actions of relaxin are mediated via its receptor, RXFP1, a transmembrane protein belonging to the leucine-rich G protein receptor family (Hsu et al 2002). Results of the present study, indicating that exposure of gilts to EV for 2 weeks from birth increased uterine RXFP1 expression at PND 14, support previous studies that showed estrogens increased porcine uterine relaxin binding (Mercado-Simmen et al 1982) as well as RXFP1 gene expression in the porcine reproductive tract (Yan et al 2008) and in a human uterine fibroblast cell line (Maseelall et al 2009). Importantly, data also show that the estrogen-induced increase in uterine RXFP1 expression observed on PND 14 is similar to that observed in adult endometrium obtained from neonatally EV-exposed gilts on PxD 12.…”
Section: Discussionsupporting
confidence: 81%
“…Actions of relaxin are mediated via its receptor, RXFP1, a transmembrane protein belonging to the leucine-rich G protein receptor family (Hsu et al 2002). Results of the present study, indicating that exposure of gilts to EV for 2 weeks from birth increased uterine RXFP1 expression at PND 14, support previous studies that showed estrogens increased porcine uterine relaxin binding (Mercado-Simmen et al 1982) as well as RXFP1 gene expression in the porcine reproductive tract (Yan et al 2008) and in a human uterine fibroblast cell line (Maseelall et al 2009). Importantly, data also show that the estrogen-induced increase in uterine RXFP1 expression observed on PND 14 is similar to that observed in adult endometrium obtained from neonatally EV-exposed gilts on PxD 12.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, Rxfp1 gene expression increased after estradiol valerate treatment from birth in the uterus of Postpartum Day 2 pigs, again indicating the positive effects of 17b-estradiol on Rxfp1 [13]. Treatment of human lower uterine segment fibroblasts in vitro with estrogen also increases Rxfp1 mRNA expression [31]. This contradicts the data in the present study, because RU486 treatment increased 17b-estradiol and Esr1 but resulted in a decrease in RXFP1.…”
Section: Regulation Of Myometrial Rxfp1contrasting
confidence: 67%
“…Relaxin binds to the 2002 discovered relaxin receptor 1 (LGR7) and with lower affinity to the closely related relaxin receptor 2 (LGR8), which are G proteincoupled transmembrane proteins with a characteristic leucinerich repeat extracellular domain [10]. Although LGR7 has recently been described in human cervical fibroblasts, its impact on human parturition remains unclear [11].…”
Section: Introductionmentioning
confidence: 99%